PENDEKATAN PEMASARAN POLITIK (POLITICAL MARKETING) DALAM PEMILIHAN UMUM - Sutarso, Joko (Universitas Muhammadiyah Surakarta, 2011)
Political Marketing Approach (Political Marketing) in Indonesia began to be known in Indonesia in the general election in the era of reform. This approach is increasingly recognized in line with the success of new parties that perform this approach in a variety of campaigns so as to obtain a significant number of seats in representative institutions. As an approach, the political marketing does not guarantee victory, but at least can provide a means of understanding that politics can be offered using a commercial product marketing approach. One of the things that are important in this approach is to attempt an understanding of the electorate by grouping them in a particular group or so-called segmentation. Each segment is considered homogeneous so that effective programs can be arranged for the group. The introduction to the audience of voters is an important part in the preparation of the election campaign program.?